(untitled) (Al-Academy, 2023)
There is no doubt that development is a human necessity and an urgent technical imperative that science imposes on all aspects of societal life. Especially in the field of graphic design, as logos are among the most prominent graphic achievements of an interactive nature with the requirements of the technical and functional era to serve the recipient and the continuity of interaction with him through a visual message sent to him constantly to remind him of what he interacted with in advance, which is known as visual identity, and during the process of developing logos especially And by providing designs that suit the contemporary technical and functional development, we often see the logo lose its visual identity. Therefore, the research presented a question that represents a problem that the research tried to solve, and it is as follows: “How can the institutional visual identity be strengthened through the design change of government slogans in accordance with contemporary requirements?The methodological framework included: the importance of research and the need for it, the purpose of the research, the limits of research and the most important terms.The theoretical framework contains two topics: the first topic: the concept of identity, the second topic: the relationship of form and content in designing the logo of the institution, and the indicators of the theoretical framework.The research procedures were: the research community: research models and methods of selection: and analysis of models:The research concluded with the results and conclusion, including:1. The general structure of the Logo Board, which was formed according to the circular body or something close to it in shape, as in Models 1 and 2.2. Logos are based on the shorthand graphic elements and symbols as in Model No. 1,2.3. Diversity of intellectual principles in designing corporate logos, losing the functional purpose of the slogan for the governmental institution